2012
DOI: 10.1371/journal.pone.0037328
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Using Ultra-High Field (7 T) MRI for Clinical Surgical Targeting

Abstract: The advantages of ultra-high magnetic field (7 Tesla) MRI for basic science research and neuroscience applications have proven invaluable. Structural and functional MR images of the human brain acquired at 7 T exhibit rich information content with potential utility for clinical applications. However, (1) substantial increases in susceptibility artifacts, and (2) geometrical distortions at 7 T would be detrimental for stereotactic surgeries such as deep brain stimulation (DBS), which typically use 1.5 T images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 30 publications
(40 reference statements)
0
82
0
Order By: Relevance
“…At 3 T MRI Balachandran et al [61] described the targeting error of T2-TSE in comparison to CT with a maximum of 0.13 mm over twelve targets. Duchin et al [62] compared T2-TSE at 7 T and 1.5 T and found distortion differences of less than one voxel size. At 7 T MRI Cho et al [27] quantified the geometrical distortions of a T2-weighted gradient-echo sequence with a mean deviation of 0.12 ± 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…At 3 T MRI Balachandran et al [61] described the targeting error of T2-TSE in comparison to CT with a maximum of 0.13 mm over twelve targets. Duchin et al [62] compared T2-TSE at 7 T and 1.5 T and found distortion differences of less than one voxel size. At 7 T MRI Cho et al [27] quantified the geometrical distortions of a T2-weighted gradient-echo sequence with a mean deviation of 0.12 ± 0.13 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited literature is currently available regarding the use of 7-tesla MRI in stereotactic biopsies [17,18]. There is a presumption that the increased field strength increases the image distortion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a good algorithm for automatic distortion correction is absent and, therefore, the application is currently not recommended even with CT fusion. The study by Duchin et al [17] compared 1.5- and 7-tesla MRI for clinical surgical targeting in 12 patients treated with deep brain stimulation for Parkinson's disease. Their analyses revealed that distances between identical landmarks on 1.5 vs. 7 T, in the mid-brain region, were <1 voxel and that the central part of the brain showed only minimal distortion.…”
Section: Discussionmentioning
confidence: 99%
“…However, it reduces the total error of the procedure and thus promotes a more comprehensive understanding of therapeutic outcomes. In that regard, 2 recent studies 29,30 investigated possible issues for neurosurgical targeting due to higher geometric distortions at 7T. Without dissent, they reported relatively small distortions in the central brain regions and concluded that targeting is feasible with 7T imaging.…”
Section: Discussionmentioning
confidence: 99%